Implementation of sustainable forest management: an application of the triple perspective typology of stakeholder theory in a case study in Sabah, Malaysia - Walter Lintangah; Norbert Weber (Technische Universität Dresden, 2015)
The progress of the concept of Sustainable Forest Management (SFM) is dynamic and its success or failure during implementation can be evaluated in different ways. In a detailed survey in four Forest Management Units (FMUs) in Sabah, the current implementation of SFM at the FMU level was assessed based on the triple perspective typology of stakeholder theory. This approach encompasses conceptual, corporate and stakeholder centric point of view. The conceptual perspective explores the SFM concept and how it relates to the FMU holder – stakeholder interaction at the FMU level, the corporate perspective examined how the FMU holders put the concept into practice and address their stakeholders, while the stakeholder perspective analyses how the stakeholders attempt to accomplish their claims and interests through the corporate-centric (FMU holders) at the management level. The stakeholder analysis provides the platform for stakeholder identification, categorization and their general perception and behaviour towards the overall performance of SFM objectives. The Stakeholder Relation Management (SRM) that integrates the FMU holders and stakeholder participation under the SFM concept were also identified. Different FMU holders are engaged with distinct objectives to be achieved, which determine their direct relationship with the stakeholders. The stakeholders were attributed to static and dynamic groups, which are determined by their existence, claims and interests, and involvement in various SFM programs and activities at the FMU level. They provided distinguished preference and agreement toward various issues and characteristics related to SFM objectives, implementation and stakeholder participation at the management level. Most of the respondents of the multi-interest stakeholder group agreed with SFM main contributions towards the elements of environmental objectives, followed by economic objectives and elements of social objectives. The approach for SFM assessment based on the different lenses of conceptual, corporate and stakeholder centric provides complementary evidence on the pragmatic implementation of SFM at the forest management level.